Hubungan Pengetahuan dan Pendidikan Ibu terhadap Status Gizi Balita - Nurmaliza Nurmaliza; Sara Herlina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the relationship between knowledge and education on the nutritional status of children under five in the Rumbai Pesisir District, Pekanbaru City. This research is a quantitative analytic study with a cross sectional approach. The results of the study based on the chi square test obtained the value of Pvalue <0.05 (<0.006 <0.05) and (<0.034 <0.05). In conclusion, there is a relationship between knowledge and education on the nutritional status of children under five. Keywords: Toddler, Education, Knowledge, Nutritional Status